MICROTEACHING DALAM JARINGAN BERBASIS LESSON STUDY DAN PENINGKATAN KETERAMPILAN MENGAJAR SERTA PENGEMBANGAN LESSON PLAN - Herry Agus Susanto; Erika Laras Astutiningtyas; Dewi Susilowati (Delta: Jurnal Ilmiah Pendidikan Matematika, 2021)
The purpose of this study is to improve skills in developing Lesson Plans and teaching skills for students. This type of research is a descriptive study with a qualitative approach. The research subjects were 11 students of the Mathematics Education Study Program, Teacher Training and Education Faculty, Universitas Veteran Bangun Nusantara Sukoharjo. The research was conducted on Microteaching Courses which were conducted based on Lesson Study. Recovery is carried out in a network using several platforms, namely: YouTube, the Learning System in the Universitas Veteran Bangun Nusantara Sukoharjo Network with the Moodle, Zoom, and WhatsApp application platforms. The method of data collection is carried out by the method of observation. The instruments used in this study were: Teaching skills assessment sheet and lesson plan assessment sheet. The two instruments are carried out to assess teaching skills and the Learning Implementation Plan in Open Lesson I, II, and III. Based on the results of the study, it was found that the change in the average score of 11 students who practiced their skills in developing Lesson Plans starting from 76.636; 84,182; 88,364. For teaching skills, the changes are as follows: 76,818; 83,909; 87,182. So the result of this research is that the implementation of Microteaching in a network based on Lesson Study can improve students' abilities in compiling Lesson Plans and student teaching skills.